EVOLUTION OF TITLES OF KUSHAN RULER (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The political situation of the period after the collapse of the Greco-Bactrian kingdom was reflected in the works of many researchers. In scientific literature, this problematic period is very well covered, first of all, in Greco-Roman and, moreover, in Chinese literature. According to the Chinese traveler and historian Zhang Jian', the Yueji tribes, defeated by the Huns, now move southward, conquer Dahya (Bactria) and settle on the northern side of Gui-shui (Amu Darya). After a certain period of time, the Yuechi confederation split into five parts, each of which was headed by a nomadic tribal elder - a tribal chief with the title of Yabgu.